Risk Management Framework in Zakat-Based Islamic Microfinance - Mahadi, Nur Farhah; Hasan, Aznan; Noor, Azman Mohd; Zakariyah, Habeebullah (Etihad: Journal of Islamic Banking and Finance, 2025)
Introduction: This study explores the potential of utilizing zakat funds or their proceeds for microfinance initiatives by developing a robust risk management framework. The framework aims to ensure prudential use of zakat resources and align with Islamic ethical and operational principles to enhance the effectiveness of zakat-based microfinance in promoting socioeconomic empowerment. Research Methods: A qualitative approach is employed to analyze the use of Islamic financial contracts such as qarḍ ḥasan, muḍarabah, musharakah, salam, and ijarah in managing portfolio risks within zakat-based microfinance institutions. Results: The findings indicate that a structured risk management framework improves the financial stability and accountability of zakat-based microfinance institutions. It provides clear parameters for prudential management and helps safeguard zakat funds against potential losses. Conclusion: This study proposes a practical framework that helps zakat institutions balance financial sustainability with their mission of socioeconomic empowerment, enhancing transparency and resilience in zakat-based microfinance.